(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both processes are involved in the development of diabetes. Diabetes is also known as Madhumeha in Ayurveda. Diabetes Mellitus has become a global problem in spite of advances in modern science. Ancient science of Ayurveda has discussed diabetes at length thousands of years ago. Number of diabetic patients are increasing in very high range. Year by year, its growing speed is very fast. In Ayurveda there are many ways to prevent diabetes mellitus and to cure its complications. Ayurvedic medications and management is very helpful and very effective in specially for diabetes. In this paper, trying to explain the hypoglycemic effect of Momordica (Karela) in diabetes mellitus (Madhumeh). Karela is specifically used as a folk medicine for diabetes. Several researches proved that it contains a hypoglycaemic or insulin-like principle, designated as ’plant-insulin’, which has been found highly beneficial in lowering the blood and urine sugar levels.